Formação continuada de professores: entre a pedagogia do afeto e a pedagogia científica - Consaltér, Evandro (2016)
In the present dissertation it is exposed a contextualized investigation of how the continued formation of teachers has been developed in schools and their contribution to the qualification of the teacher´s pedagogical practice. The study is based on the following guiding questions: How has continuing education been conducted in schools? What issues have been addressed? For which professionals have these formative events been conducted? What epistemological influences pervade these formative events? What do teachers understand by continuing education? What is the contribution that formative events developed in schools offer to the teachers' pedagogical practice? To answer these questions, first of all, a bibliographic research was carried out having by reference criterion two formative conceptions: one, called the affection pedagogy, has a marketing appeal and points out love and affection as self-sufficient elements to deal with solving all educational problems; the other, named scientific pedagogy, has a theoretical epistemological appeal and understands the continued formation not as an isolated event, but as a continuous search for a better contextualization and understanding of the formative processes. Subsequently, the study makes use documentary and empirical material, from the 11 state schools of the north region of Rio Grande do Sul selected for the present investigation. The documentary material is composed of the projects of continuous formation of teachers developed in 2015 by the selected schools. The empirical material is composed of the results produced from the electronic questionnaire sent to the teachers of the schools by Google Forms, in which they were asked about continuing education, the contributions of training courses offered by their schools among other issues that we consider relevant to the research. Finally, the study makes a cross among the bibliographical research, the documentary analysis and the empirical indicatives produced from the questionnaires. As a result of the research it is possible to infer that the affection pedagogy becomes a tempting alternative and comfortable with the exhaustive search for a qualification epistemological theoretical, making room for the perpetuation of self-help literature in education. We consider that this normative bias, as it has been conducted, fulfills only the anesthetic function of inebriate teachers, taking away their critical capacity. On the other hand, it also becomes incoherent only to judge or condemn the affection pedagogy. We consider that when carried out an analysis careful of the presuppositions of this pedagogy, accompanied by an academic treatment based on a powerful reference, which extrapolates a superficial analysis, it can be consolidated into a potential material to be placed as a starting point for continuing education. Through the study, we also consider that it is necessary to review the ways in which continuing teacher training is developed in schools. A formation which, as the nomenclature itself emphasizes, should therefore be a continuous process, which in the understanding of scientific pedagogy is made and remakes with a lucid spirit and innovative through a formative posture that is really enlightening consistent and scientifically grounded.